Outcome of Women with Previous Cesaerian Section At A Tertiary Care Hospital in Eastern Nepal - Agrawal, Ajay; Chhetri, S; Thakur, A; Agrawal, S; Basnet, P (Health Renaissance, 2015)
Background: Pregnant women with previous caesarean section are increasing due to the liberal use of caesarean section in first pregnancy due to multifactorial reason. The risks, benefits, and relative safety of vaginal birth after caesarean (VBAC) have been subject of interest for well over 100 years. Thus mutual understanding between the treating obstetrician and patient herself is a core towards achieving good maternal and perinatal outcome considering all the risk and benefit in women with previous caesarean section. Objective: The aim was to analyze the maternal and perinatal outcome in pregnant women with previous caesarean section. Methods: In this prospective observational study, 300 women with singleton pregnancy in cephalic presentation with previous one lower segment caesarean section (LSCS) having inter pregnancy interval ≥ 18 months presenting at ≥ 37-41 week period of gestation admitted for delivery were enrolled and various maternal and perinatal outcome were noted. Results: Caesarean delivery rate during the study period was 26.95%. Eighty percent of eligible women opted for trial of labor. Successful vaginal birth after caesarean section was 29%. Elective repeat caesarean delivery was 19.66%. The rate of failed VBAC was 51%. Failed VBAC increased with increasing weight of baby. There was no difference in mean birth weight among patient who had successful VBAC, who refused VBAC and who had failed VBAC. Mode of delivery had no significant effect on the number of neonatal intensive care unit admission and number of still births. DOI: http://dx.doi.org/10.3126/hren.v12i1.11980 Health Renaissance 2014;12(1):18-23